Immigration and the occupational choice of natives: A factor proportions approach - Javier Ortega; Gregory Verdugo (Institute for the Study of Labor (IZA), 2011)
This paper evaluates the impact of immigration on the labor market outcomes of natives in France over the period 1962-1999. Combining large (up to 25%) extracts from six censuses and data from Labor Force Surveys, we exploit the variation in the immigrant share across education/experience cells and over time to identify the impact of immigration. In the Borjas (2003) specification, we find that a 10% increase in immigration increases native wages by 3%. However, as the number of immigrants and the number of natives are positively and strongly correlated across cells, the immigrant share may not be a good measure of the immigration shock. When the log of natives and the log of immigrants are used as regressors instead, the impact of immigration on natives' wages is still positive but much smaller, and natives' wages are negatively related to the number of natives. To understand this asymmetry and the positive impact of immigration on wages, we explore the link between immigration and the occupational distribution of natives within education/experience cells. Our results suggest that immigration leads to the reallocation of natives to better-paid occupations within education/experience cells.
urn:nbn:de:101:1-201104113240
Keywords: J15; J31; 330; immigration; occupations; Einwanderung; Bevölkerung; Berufswahl; Qualifikation; Lohn; Schätzung; Frankreich